The Abundance of Special Autonomy Funds: An Ironic Portrait of Aceh's Poverty Alleviation - Ikhsan Ikhsan; Ikhwan Rahmatika Latif; Vellayati Hajad; Effendi Hasan; Muntaha Mardhatillah; Herizal Herizal (Journal of Government and Civil Society, 2023)
This article examines the financial management of the government of Aceh, which is supported by special autonomy funds. It is a war compensation and recovery from the tsunami disaster following the signing of a peace accord between the Free Aceh Movement (GAM) and the Government of Indonesia for development to increase the Acehnese people's well-being, disbursed by the central government. But the governance of the special autonomy fund it runs has not been able to help Aceh get out of poverty according to national standards. The article employed a descriptive qualitative approach, then purposive sampling used by the authors as the technique to identify people to interview about Aceh's poverty and special autonomy fund issues. Open publications, whether they be official government documents such as rules or decisions, newspapers or magazines, or scientific references such as books or journals were secondary data used by authors. The findings revealed that the management of the special autonomy fund lacks a mature grand design, such that the management rules change annually and are also influenced by the tug-of-war between the Aceh government and the region/city governments. Then, the principle of accountability was not properly implemented, so these two findings were unable to affect the substance of the poverty sector in Aceh, causing Aceh's poverty to consistently fall below the national average.Artikel ini mengkaji masalah pengelolaan keuangan pemerintah Aceh yang ditopang oleh dana otonomi khusus. Dana Otonomi Khusus ini merupakan untuk pemulihan dari bencana tsunami dan kompensasi perang setelah penandatanganan kesepakatan damai antara Gerakan Aceh Merdeka (GAM) dan Pemerintah Indonesia yang bertujuan untuk pembangunan peningkatan kesejahteraan rakyat Aceh, yang dikucurkan oleh pemerintah pusat. Namun tata kelola dana otsus yang dijalankannya belum mampu membantu Aceh keluar dari zona kemiskinan sesuai standar nasional. Artikel ini menggunakan pendekatan kualitatif deskriptif, kemudian purposive sampling digunakan oleh penulis sebagai teknik untuk mengidentifikasi orang-orang yang akan diwawancarai tentang masalah kemiskinan dan dana otonomi khusus Aceh. Publikasi terbuka, baik berupa dokumen resmi pemerintah seperti peraturan atau keputusan, surat kabar atau majalah, atau referensi ilmiah seperti buku atau jurnal merupakan data sekunder yang digunakan oleh penulis. Temuan menunjukkan bahwa pengelolaan dana otsus tidak memiliki grand design yang matang, sehingga aturan pengelolaannya berubah setiap tahun dan juga dipengaruhi oleh tarik ulur antara pemerintah Aceh dengan pemerintah daerah/kota. Kemudian, prinsip akuntabilitas tidak diterapkan dengan baik, sehingga tidak mampu mempengaruhi permasalahan Â substantif sektor kemiskinan di Aceh dan menyebabkan kemiskinan Aceh secara konsisten berada di bawah rata-rata nasional.